EFEKTIVITAS PENERAPAN TEKNIK FREE WRITING TERHADAP KETERAMPILAN MENULIS CERITA PENDEK PESERTA DIDIK KELAS XI DI SMK SANGKURIANG 1 CIMAHI - Nur Fadila, Alya (Program Studi Tadris Bahasa Indonesia, 2023)
This research is motivated by the low short story writing ability of vocational students in the Indonesian language subject. This study aims to see the effectiveness of free writing techniques through students' short story writing skills. The method in this research is quantitative research. The subjects of this study were students of class XI at SMK Sangkuriang 1 Cimahi. The instruments used in this study were interview sheets, response questionnaires to learning, and student questionnaires. The material used in this research is writing short stories. Pretest and posttest data on the free writing technique of short story writing skills were analyzed using IBM SPSS Statistics version 22 software. The results of this study indicate that the analysis of short story writing ability before the free writing technique was applied showed that there were deficiencies in the experimental class compared to the control class. The experimental class got 69,33 and the control class got 73,17. Analysis of short story writing ability after applying free writing techniques showed a significant increase in results. The experimental class got a score of 84,33 while the control class got a score of 78,17. Learning with the free writing technique shows the effectiveness of students' writing skills because they get an increase of 6,16. Keywords: Effectiveness, free writing techniques, short story writing skills.